THE ROLE OF IDEOLOGICAL IMMUNITY IN THE FORMATION OF MORAL PERSONS IN ADOLESCENTS - M. Turdieva (INTERNATIONAL JOURNAL OF SOCIAL SCIENCE & INTERDISCIPLINARY RESEARCH ISSN: 2277-3630 Impact factor: 8.036, 2023)
This article talks about social factors that affect the development of moral qualities and certain aspects of adolescence. Adolescents have a great need for adult trust, and the most favorable conditions for adults to influence and educate adolescents are opportunities such as common work.